Capacity Building in Indonesian Banking Sector: A Review on Sustainable Financial Affairs - Indra Siswanti; Darwin Darwin; Lenny Christina; Maharini Maharini; Ahmad Hidayat (Universitas Mercu Buana, 2022)
The implementation of sustainable finance is still a challenge in the banking sector. One important element is the availability of Human Resources who understand the sustainable economy. Banking institutions need to prepare professional and quality Human Resources who are able to apply the principles of sustainable finance so that they can create products or services in an effort to improve services to customers in the banking sector.Objectives: To support the Indonesian government's program for implementing sustainable financial programs, especially in the banking sector of Indonesia, a good strategy is needed to prepare and increase capacity building. The purpose of this research is to analyze the effect of Capacity Building in the implementation of Sustainable Finance in the banking sector of Indonesia.Methodology: This study used quantitative methods with 100 employees at banking institutions as the object of research. The research sampling technique uses simple random sampling with data analysis using SEM PLS.Finding: This research proves that leadership and talent management affect capacity building in the Banking sector towards implementing sustainable finance. This study proved that:1) direct influence of leadership talent management and capacity building to financial sustainability, 2) indirect influence of leadership and talent management on financial sustainability through capacity building.Conclusion: This research proves the influence of leadership and talent management on financial sustainability mediated by capacity buildingKeywords: Banking, Strategy, Capacity Building, Financial Sustainability.